Tool support for the Test Template Framework. (13th July 2012) - Cristiá, Maximiliano; Albertengo, Pablo; Frydman, Claudia; Plüss, Brian; Monetti, Pablo Rodríguez
SUMMARY This paper describes tool support that has been implemented for the Test Template Framework (TTF). The TTF is a model‐based testing (MBT) method that is especially well suited for unit testing from Z specifications. Although the TTF is a sound MBT method and it has been widely referenced since its first publication, attention in recent years has decayed. In fact, some have argued that generating abstract test cases following the TTF is a manual task requiring its users to perform complex predicate manipulations. This paper shows that these observations are dubious by describing Fastest, a tool that implements solutions for all these issues and, according to many experiments, produces abstract test cases for more than 80% of the satisfiable test specifications. Furthermore, it is claimed that Fastest fulfils the needs of the Z user community regarding MBT tools, which is supported with a range of case studies. Copyright © 2012 John Wiley & Sons, Ltd.